2022
DOI: 10.3389/fcell.2022.817965
|View full text |Cite
|
Sign up to set email alerts
|

CD93 Correlates With Immune Infiltration and Impacts Patient Immunotherapy Efficacy: A Pan-Cancer Analysis

Abstract: Background: The clinical implementation of immune-checkpoint inhibitors (ICIs) targeting CTLA4, PD-1, and PD-L1 has revolutionized the treatment of cancer. However, the majority of patients do not derive clinical benefit. Further development is needed to optimize the approach of ICI therapy. Immunotherapy combined with other forms of treatment is a rising strategy for boosting antitumor responses. CD93 was found to sensitize tumors to immune-checkpoint blocker therapy after the blockade of its pathway. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Furthermore, differential expression analysis revealed increased proportions and degrees of expression of immunosuppression-related genes, such as RGS1, in CXCR6-positive T cells ( Figure 1B , left panel ). Examination of CXCL16-positive myeloid cells revealed enrichment of well-known immunosuppressive markers/phenotypes (C5Ar1 and CXCR4) ( 28 31 ) as well as inflammatory myeloid cells (CD93 and HLA-DPB1) ( 32 35 ), suggesting increased pleiotropic RNA expression in these subsets of GBM cells ( Figure 1B , right panel ).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, differential expression analysis revealed increased proportions and degrees of expression of immunosuppression-related genes, such as RGS1, in CXCR6-positive T cells ( Figure 1B , left panel ). Examination of CXCL16-positive myeloid cells revealed enrichment of well-known immunosuppressive markers/phenotypes (C5Ar1 and CXCR4) ( 28 31 ) as well as inflammatory myeloid cells (CD93 and HLA-DPB1) ( 32 35 ), suggesting increased pleiotropic RNA expression in these subsets of GBM cells ( Figure 1B , right panel ).…”
Section: Resultsmentioning
confidence: 99%
“… 34 Both anti- CD44 antibody and CD44 deficiency in mice mitigated liver steatosis, attenuated adipose inflammation, and improved glucose tolerance in diet-induced obese mice. 35 , 36 CD93 is also involved in NK cell immune tolerance and is negatively correlated with NK cells, 37 and anti- CD93 antibodies can increase the infiltration of NK cells. 38 In our study, B. uniformis transplantation statistically reduced the expression of hepatic CD44 and CD93 , offering another considerable mechanism by which it enhances NK cell infiltration and activation.…”
Section: Discussionmentioning
confidence: 99%
“…6 Zhang et al found that CD93 is a biomarker for a variety of malignancies and is associated with immune infiltration, and that inhibition of the CD93 pathway affected the outcome of immunotherapy. 7 Surfactant protein A1 (SFTPA1) is a member of the C-type lectin subfamily. Lu et al performed immunofiltration analysis and revealed that it is quite important in the innate immune response.…”
Section: Introductionmentioning
confidence: 99%
“…Immune infiltration was the focus of immunotherapy 6 . Zhang et al found that CD93 is a biomarker for a variety of malignancies and is associated with immune infiltration, and that inhibition of the CD93 pathway affected the outcome of immunotherapy 7 . Surfactant protein A1 (SFTPA1) is a member of the C‐type lectin subfamily.…”
Section: Introductionmentioning
confidence: 99%